High-strength high-temperature-resistant cement-based grouting material and preparation method thereof

By introducing high-aluminum aggregate, fiber and concave-convex rod-soil insert modified Brunei glue into the cement-based grout material, the problem of insufficient compressive strength ratio and thermal shock stability in high-temperature environments is solved, and its high-temperature resistance and compressive strength are significantly improved.

CN119751002AActive Publication Date: 2025-04-04HUAXIN CEMENT CO LTD +1

Patent Information

Application Number
CN202411920806.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-04
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The existing cement-based grouting materials have insufficient compressive strength ratio and thermal shock stability in high-temperature environments, which limits their promotion and application in high-temperature use environments.

Method used

High-strength high-temperature resistant cement-based grouting materials are used, and their compositions include cement, mineral powder, micro-bead powder, aggregate, fiber and anti-slump-retaining composite modifier. By introducing materials such as high-alumina aggregate and fiber, the high-temperature resistance and compressive strength of grouting materials are improved, and the Brunei glue is modified to improve the flowability and structural compactness of the aggregate through the concave and convex rod soil intercalation.

Benefits of technology

It significantly improves the high temperature resistance, compressive strength and thermal shock stability of the grouting material, ensures that it has good mechanical properties at high temperatures of 200-300℃, and is suitable for construction needs in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005207927530000051
    Figure BDA0005207927530000051
  • Figure BDA0005207927530000061
    Figure BDA0005207927530000061
Patent Text Reader

Abstract

The invention discloses a high-strength and high-temperature-resistant cement-based grouting material which comprises the following components in percentage by mass: 12-40% of cement, 1-17% of mineral powder, 1-10% of microbead powder, 30-60% of aggregate, 0.5-1.0% of fiber, 0.01-0.03% of an anti-settling-slump retaining composite modifier, 0.10-0.25% of a water reducing agent, 0-0.03% of an early expanding agent and 0-1.0% of a defoaming agent, the ratio of water to material is 0.12-0.14, and the anti-settling-slump-retaining composite modifier is intercalated modified welan gum. The cement, the mineral powder and the microbead powder are used as main gelling components, and are combined with functional components such as the high-temperature-resistant aggregate, the fibers and the anti-settling-slump-retaining composite modifier, so that the obtained grouting material has relatively high high-temperature resistance, compressive strength ratio and thermal shock resistance, also has relatively good working performance and relatively high compressive strength, and is wide in applicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to a high-strength and high-temperature resistant cement-based grouting material and a preparation method thereof. Background Art

[0002] Cement-based grouting materials are widely used in equipment foundation secondary grouting, anchor bolt anchoring, building structure reinforcement and other projects due to their early strength, micro expansion and good working performance. Existing grouting materials usually focus on fluidity, strength, expansion rate and other properties, and do not involve research and improvement on thermal shock stability. The lack of compressive strength ratio and thermal shock stability under high temperature environment is the main factor restricting the promotion and application of cement-based grouting materials in high temperature use environment.

[0003] Patent application CN107244858A discloses a high temperature resistant grouting material, which is made of the following raw materials in parts by weight: 100 parts of cement, 120-130 parts of quartz sand, 50-60 parts of fly ash, 15-16 parts of silicon powder, 4-7 parts of titanium boride, 12-14 parts of carbon fiber, 20-25 parts of steel fiber, 5-8 parts of expansion agent, 1-3 parts of water reducer, 1-2 parts of defoamer, 2-5 parts of antifreeze agent, 0.5-1.5 parts of early strength agent, 0.5-0.8 parts of retarder; it has the characteristics of high strength, long service life, and can withstand high temperatures above 1000°C; but it does not involve modification of the thermal shock stability of the grouting material, cannot adapt to the rapid changes in the ambient temperature of use, and the fluidity of the obtained grouting material is poor. Summary of the invention

[0004] In order to overcome the deficiencies of the above-mentioned prior art, the main purpose of the present invention is to provide a high-strength and high-temperature resistant cement-based grouting material and a preparation method thereof. The grouting material has high high temperature resistance, compressive strength ratio and thermal shock stability, and has good working performance and high compressive strength.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme:

[0006] A high-strength and high-temperature resistant cement-based grouting material, wherein the components and their mass percentages include: 12-40% cement, 1-17% mineral powder, 1-10% microbead powder, 30-60% aggregate, 0.5-1.0% fiber, 0.01-0.03% anti-settling-collapse-preserving composite modifier, 0.10-0.25% water reducer, 0-0.03% early expansion agent, and 0-1.0% defoamer; the water-to-material ratio is 0.12-0.14, wherein the anti-settling-collapse-preserving composite modifier is intercalated modified Brunei rubber.

[0007] In the above scheme, the intercalation modified Brunei rubber is attapulgite intercalation modified Brunei rubber.

[0008] Furthermore, the preparation method of the anti-settling-collapse-preserving composite modifier is: adding attapulgite to a Brunei glue aqueous solution, carrying out a water bath reaction under a protective atmosphere and stirring conditions, centrifuging, washing, filtering, and drying to obtain the anti-settling-collapse-preserving composite modifier.

[0009] In the above scheme, the particle size of the attapulgite is 400-600 mesh.

[0010] In the above scheme, the concentration of the Brunei glue solution is 0.08-0.12wt%.

[0011] In the above scheme, the solid-to-liquid ratio of the attapulgite to the Brunei glue aqueous solution is 1g:40-60mL.

[0012] In the above scheme, the protective atmosphere can be nitrogen or argon.

[0013] In the above scheme, the temperature used for the water bath reaction is 70-80°C and the time is 22-26h.

[0014] In the above scheme, the temperature used in the drying step is 60-70° C. and the time is 6-12 hours.

[0015] In the above scheme, the cement is one or more of silicate cement, ordinary silicate cement, and sulphoaluminate cement, and the strength grade is above 52.5.

[0016] In the above scheme, the mineral powder is one or more of S95 mineral powder or ultrafine mineral powder; the specific surface area of ​​S95 mineral powder is 300-500m 2 / kg, the specific surface area of ​​ultrafine mineral powder is 600~1000m 2 / kg.

[0017] In the above scheme, the microbead powder is fly ash extract, and its bulk density is ≥700kg / m 3 , silicon dioxide content ≥50%.

[0018] In the above scheme, the aggregate includes high-aluminum aggregate, and the content of the high-aluminum aggregate is more than 20wt%.

[0019] Furthermore, the particle size of the high-alumina aggregate is 0 to 1 mm.

[0020] Furthermore, the aggregate further comprises one or more of quartz sand with a mesh size of 40 to 70 and quartz sand with a mesh size of 20 to 40.

[0021] In the above scheme, the fiber is one or more of polyethylene fiber with an average diameter of 0.02-0.04 mm, polypropylene fiber with an average diameter of 0.02-0.04 mm, basalt fiber with an average diameter of 0.01-0.03 mm, and steel fiber with an average diameter of 0.18-0.22 mm, and the average fiber length is 6-10 mm.

[0022] In the above scheme, the water reducing agent is a powdered polycarboxylic acid water reducing agent, and the water reducing rate of the mortar is ≥20%.

[0023] In the above scheme, the early expansion agent is an azo expansion agent.

[0024] Furthermore, the azo expansion agent may specifically be azodicarbonamide or azobisisobutyronitrile.

[0025] In the above scheme, the defoaming agent is a polyether-modified silicone defoaming agent.

[0026] The preparation method of the above-mentioned high-strength and high-temperature resistant cement-based grouting material comprises the following steps:

[0027] 1) Weigh the raw materials, and the components and their mass percentages include: cement 12-40%, mineral powder 1-17%, micro-bead powder 1-10%, aggregate 30-60%, fiber 0.5-1.0%, anti-settling-collapse composite modifier 0.01-0.03%, water reducer 0.10-0.25%, early expansion agent 0-0.03%, defoamer 0-1.0%;

[0028] 2) mixing the weighed raw materials to obtain a high-strength and high-temperature resistant cement-based grouting material premix;

[0029] 3) The premix and water are mixed and stirred evenly at a water-to-material ratio of 0.12 to 0.14 to obtain a high-strength and high-temperature resistant cement-based grouting material.

[0030] The principle of the present invention is:

[0031] A large amount of mineral admixtures such as mineral powder and microbeads can be introduced into the high-strength and high-temperature resistant cement-based grouting of the present invention, which can greatly improve the residual strength of the mineral admixture at high temperature, and can improve the working performance of the grouting material, making the grouting material easy to construct. Among the introduced fibers, polyethylene fiber has the characteristics of low density, high strength, chemical corrosion resistance, high temperature resistance, low elongation at break, etc. It can be evenly dispersed in the grouting material and can improve the high-temperature mechanical properties of the grouting material. Under high temperatures of 200 to 300°C, it can be used as a sacrificial material to provide interconnecting holes to prevent the expansion stress and bursting of water vapor in the capillaries at high temperatures, and prevent the internal stress accumulation caused by the inconsistent thermal expansion coefficients of aggregates and cement stone at high temperatures, so it can especially improve the thermal shock stability of the grouting material; basalt fiber has good high-temperature resistance and can withstand high temperatures above 1400°C, which can prevent cement-based materials from bursting at ultra-high temperatures.

[0032] The early expansion agent introduced can improve the expansion performance of the grouting material in the plastic stage, so that the grouting material can play a role of micro-expansion during application, improve the tightness of the bonding between the grouting material and the equipment foundation, and improve the application effect.

[0033] The high-strength and high-temperature resistant grouting material of the invention is added with a high-performance water reducing agent and a defoaming agent and is combined with high-temperature resistant aggregates, and has a reasonable gradation, thereby ensuring good working performance of the obtained grouting material.

[0034] The present invention adopts a high-aluminum aggregate-based aggregate system and uses high-aluminum aggregate as a high-temperature resistant aggregate. On the one hand, the high-aluminum aggregate has a high temperature resistance temperature of 1500°C, which can significantly improve the high-temperature resistance of the grouting material; on the other hand, the high-aluminum aggregate has high strength, is porous, and has a rough surface, which can improve the bonding performance of the slurry and the aggregate, thereby significantly improving the compressive strength of the grouting material. However, due to the high water absorption rate and high apparent density of high-aluminum aggregate, there are problems such as easy sedimentation and large fluidity loss in a large fluid system such as a grouting material.

[0035] In view of the above technical problems, the present invention further adopts attapulgite intercalation modified Brunei rubber as an anti-settling-slump-preserving composite modifier, which can effectively improve the adverse effects of aggregates and traditional thickeners on working performance. Its working principle is: because Brunei rubber molecules have a large anion charge density, they have a strong complexation with calcium ions on the surface of cement colloid particles, and their adsorption effect on the surface of cement particles is stronger than that of polycarboxylate water-reducing agent molecules. They are easy to produce a competitive adsorption effect with polycarboxylate water-reducing agent, which can easily cause the effect of water-reducing agent in dispersing cement particles to be significantly weakened, resulting in poor working performance; after the original Brunei rubber is modified with attapulgite by the intercalation method, the slow release of Brunei rubber components can be achieved, and the three-dimensional network structure of the Brunei rubber solution is not changed, thereby improving the compatibility between Brunei rubber and other admixtures. It can effectively improve the competitive adsorption effect of Brunei rubber and polycarboxylate water reducer, and has no obvious effect on the self-generated thickening and anti-segregation stratification effects of Brunei rubber; and the addition of attapulgite can promote the secondary hydration of cement, consume calcium hydroxide to generate more CSH gel to fill the hardened cement paste, reduce cracks and macropores, and improve the density of the structure, thereby significantly improving the high temperature resistance of the grouting material.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1) The present invention uses cement, mineral powder and micro-bead powder as the main gelling components, combined with high temperature resistant aggregate and fiber, etc., which can effectively improve the mechanical properties and high temperature resistance of the obtained grouting material;

[0038] 2) The present invention uses attapulgite intercalation modified Brunei rubber as an anti-settling-collapse composite modifier, which can effectively improve the problems of easy settlement and large fluidity loss caused by aggregates and traditional thickeners, and ensure the working performance of the obtained grouting material; at the same time, it can improve the density of the structure and further improve the high temperature resistance of the grouting material;

[0039] 3) The high-strength and high-temperature resistant grouting material of the present invention has a 28d compressive strength greater than 90MPa under standard curing conditions, which can meet most grouting construction strength requirements, and some are higher than 120MPa. It can be used as a high-temperature resistant and ultra-high-strength grouting material with special operation requirements, and has a wide applicability. DETAILED DESCRIPTION

[0040] The present invention is further described below in conjunction with specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] In the following embodiments, the preparation method of the anti-settling-collapse-preventing composite modifier adopted comprises the following steps: weighing 5 g of attapulgite and adding it to 250 mL of 0.1 wt% original Brunei glue aqueous solution, reacting for 24 h under N2 atmosphere, stirring and 75°C water bath conditions, centrifuging, washing the separated product with deionized water, filtering, and vacuum drying at a drying temperature of 65°C for 6-12 h to obtain the anti-settling-collapse-preventing composite modifier.

[0042] In the following examples, the water reducing agent used is a powdered polycarboxylic acid water reducing agent, and the water reducing rate of the mortar is 30%; the early expansion agent used is azodicarbonamide.

[0043] The defoamer used is the polyether modified silicone defoamer P803 provided by Germany's Mingling Chemical.

[0044] Example 1

[0045] A high-strength and high-temperature resistant cement-based grouting material, wherein the preparation materials and their mass percentages include: 24.98% cement, 15.7% mineral powder, 4% microbead powder, 55% aggregate, 0.05% fiber, 0.02% anti-settling-collapse composite modifier, 0.18% water reducer, 0.02% early expansion agent, 0.05% defoamer, and a water-to-material ratio of 0.13; wherein the cement is ordinary Portland cement with a strength grade of 52.5; the mineral powder is S95 mineral powder; the fiber includes polypropylene fiber with a length of 6 mm and an average diameter of 0.02 mm and basalt fiber with a length of 8 mm and an average diameter of 0.02 mm (the mass ratio of the two is 1:1); the aggregate is 0-1 mm high-aluminum aggregate;

[0046] The preparation method thereof comprises the following steps:

[0047] 1) Weighing the raw materials: weigh the raw materials of the above components according to the proportion;

[0048] 2) After fully mixing all the weighed components, a high-strength and high-temperature resistant cement-based grouting material premix is ​​obtained;

[0049] 3) The premix and water are mixed and stirred evenly at a water-to-material ratio of 0.13 to obtain a high-strength and high-temperature resistant cement-based grouting material premix.

[0050] Example 2

[0051] A high-strength, high-temperature resistant cement-based grouting material, the preparation method of which is substantially the same as that of Example 1, except that the preparation materials and their mass percentages include: cement, mineral powder, microbead powder, aggregate, fiber, anti-settling-collapse composite modifier, water reducer, early expansion agent, and defoamer are 40.98%, 8.64%, 5%, 45%, 0.05%, 0.02%, 0.24%, 0.02%, and 0.05%, respectively; the water-to-material ratio is 0.13; wherein The cement comprises ordinary Portland cement (95wt%) and sulphoaluminum cement (5wt%) with a strength grade of 52.5, the mineral powder is S95 mineral powder, the fibers comprise polypropylene fibers with an average length of 6mm and basalt fibers with an average length of 8mm (the mass ratio of the two is 1:1); the aggregate consists of 0-1mm high-alumina aggregate (40.0wt%), 30-50 mesh quartz sand (33.3wt%) and 40-70 day quartz sand (26.7wt%).

[0052] Example 3

[0053] A high-strength and high-temperature resistant cement-based grouting material, the preparation method of which is substantially the same as that of Example 1, except that: the preparation materials and their mass percentages include: 24.98% cement, 15.7% mineral powder, 4% microbead powder, 55% aggregate, 0.05% fiber, 0.02% anti-settling-collapse composite modifier, 0.18% water reducer, 0.02% early expansion agent, and 0.05% defoamer; the water-to-material ratio is 0.13; wherein the cement is ordinary Portland cement with a strength grade of 52.5, the mineral powder is ultrafine mineral powder, and the fiber is polypropylene fiber with an average length of 6 mm and an average diameter of 0.02 mm; the aggregate is composed of 0-1 mm high-aluminum aggregate (40.0wt%), 30-50 mesh quartz sand (21.6wt%), and 40-70 day quartz sand (38.4wt%).

[0054] Comparative Example 1

[0055] A grouting material, the preparation method of which is substantially the same as that of Example 1, except that: the preparation materials and their mass percentages include: 24.98% cement, 15.7% mineral powder, 4% microbead powder, 55% aggregate, 0.05% fiber, 0.02% thickener (400 viscosity hydroxypropyl methylcellulose HPMC), 0.02% water reducer, 0.18% early expansion agent, 0.02% defoamer, and a water-to-material ratio of 0.13; wherein the cement is ordinary Portland cement with a strength grade of 52.5, the mineral powder is S95 mineral powder, the fibers include polypropylene fibers with a length of 6 mm and an average diameter of 0.02 mm and basalt fibers with a length of 8 mm and an average diameter of 0.02 mm (the mass ratio of the two is 1:1), the early expansion agent is an azo compound; and the aggregate is a 0-1 mm high-aluminum aggregate.

[0056] Comparative Example 2

[0057] A grouting material, the preparation method of which is substantially the same as that of Example 1, except that: the preparation materials and their mass percentages include: 24.98% cement, 15.7% mineral powder, 4% microbead powder, 55% aggregate, 0.05% fiber, 0.001% Brunei rubber, 0.019% attapulgite, 0.18% water reducer, 0.02% early expansion agent, 0.05% defoamer, and a water-to-material ratio of 0.13; wherein the cement is ordinary Portland cement with a strength grade of 52.5, the mineral powder is S95 mineral powder, the fibers include polypropylene fibers with an average length of 6 mm and an average diameter of 0.02 mm and basalt fibers with an average length of 8 mm and an average diameter of 0.02 mm (the mass ratio of the two is 1:1), the early expansion agent is an azo compound; and the aggregate is a 0-1 mm high-aluminum aggregate.

[0058] The high temperature resistant cement-based grouting materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were subjected to performance tests according to the Technical Specification for Application of Cement-Based Grouting Materials (GB / T 50448-2015) and the Technical Specification for Application of Heat-Resistant Concrete (YB / T 4252-2011), respectively. The results are shown in Table 1.

[0059] Table 1 Performance test results of cement-based grouting materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2

[0060]

[0061]

[0062] Note: “—” indicates that there are no relevant indicator requirements in this standard.

[0063] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

Claims

1. A high-strength and high-temperature resistant cement-based grouting material, characterized in that: The components and their mass percentages include: 12-40% cement, 1-17% mineral powder, 1-10% microbead powder, 30-60% aggregate, 0.5-1.0% fiber, 0.01-0.03% anti-settling-collapse-preserving composite modifier, 0.10-0.25% water reducer, 0-0.03% early expansion agent, and 0-1.0% defoamer; the water-to-material ratio is 0.12-0.14; wherein the anti-settling-collapse-preserving composite modifier is intercalated modified Brunei rubber.

2. The high-strength and high-temperature resistant cement-based grouting material according to claim 1, characterized in that: The intercalation modified Brunei rubber is attapulgite intercalation modified Brunei rubber.

3. The high-strength and high-temperature resistant cement-based grouting material according to claim 1, characterized in that: The preparation method of the anti-settling-collapse-preserving composite modifier comprises the following steps: adding attapulgite into a Brunei glue aqueous solution, carrying out a water bath reaction under a protective atmosphere and stirring conditions, centrifuging, washing, filtering, and drying to obtain the anti-settling-collapse-preserving composite modifier.

4. The high-strength and high-temperature resistant cement-based grouting material according to claim 3, characterized in that: The water bath reaction is carried out at a temperature of 70 to 80° C. and for a time of 22 to 26 hours.

5. The high-strength and high-temperature resistant cement-based grouting material according to claim 1, characterized in that: The cement is one or more of silicate cement, ordinary silicate cement and sulphoaluminate cement; and the strength grade is above 52.

5.

6. The high-strength and high-temperature resistant cement-based grouting material according to claim 1, characterized in that: The mineral powder is one or more of S95 mineral powder or ultrafine mineral powder; the specific surface area of ​​S95 mineral powder is 300-500m 2 / kg, the specific surface area of ​​ultrafine mineral powder is 600~1000m 2 / kg; microbead powder is fly ash extract, and its bulk density is ≥700kg / m 3 , silicon dioxide content ≥50%.

7. The high-strength and high-temperature resistant cement-based grouting material according to claim 1, characterized in that: The aggregate comprises high-aluminum aggregate, wherein the content of the high-aluminum aggregate is more than 20wt%.

8. The high-strength and high-temperature resistant cement-based grouting material according to claim 1, characterized in that: The fibers are one or more of polyethylene fibers with an average diameter of 0.02-0.04 mm, polypropylene fibers with an average diameter of 0.02-0.04 mm, basalt fibers with an average diameter of 0.01-0.03 mm, and steel fibers with an average diameter of 0.18-0.22 mm; and the average length of the fibers is 6-10 mm.

9. The high-strength and high-temperature resistant cement-based grouting material according to claim 1, characterized in that: The water reducing agent is a powdered polycarboxylic acid water reducing agent, and the mortar water reducing rate is ≥20%; the early expansion agent is an azo expansion agent.

10. The method for preparing the high-strength and high-temperature resistant cement-based grouting material according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh the raw materials, and the components and their mass percentages include: cement 12-40%, mineral powder 1-17%, micro-bead powder 1-10%, aggregate 30-60%, fiber 0.5-1.0%, anti-settling-collapse composite modifier 0.01-0.03%, water reducer 0.10-0.25%, early expansion agent 0-0.03%, defoamer 0-1.0%; 2) mixing the weighed raw materials to obtain a high-strength and high-temperature resistant cement-based grouting material premix; 3) The premix and water are mixed and stirred evenly at a water-to-material ratio of 0.12 to 0.14 to obtain a high-strength and high-temperature resistant cement-based grouting material.

Citation Information

Patent Citations

  • Cement-based high-temperature-resistant grouting material and preparation method thereof

    CN107244858A

  • Heat-resistant cement-based grouting material and preparation method thereof

    CN109592950A

  • Tackifying and shear strength improving agent, oil-based mud flushing fluid as well as preparation method and application of oil-based mud flushing fluid

    CN115141617A

  • Sleeve grouting material for prefabricated components and preparation method therefor

    WO2021128629A1

Cited By

  • High-strength and high-ductility composite concrete for roadbed reinforcement and preparation method thereof

    CN121651800A